Contribution of indoor microenvironments to the daily inhaled dose of air pollutants in children. The importance of bedrooms. (October 2020) - Lizana, Jesus; Almeida, Susana Marta; Serrano-Jiménez, Antonio; Becerra, Jose Antonio; Gil-Báez, Maite; Barrios-Padura, Angela; Chacartegui, Ricardo
Abstract: Indoor air quality plays an important role in children's wellbeing and performance. The primary attention of previous research is focused on the air quality in school environments, but time at school only represent 27% of the daily schedule. This paper analyses a broad spectrum of volatile organic compounds and aldehydes in different indoor microenvironments, according to typical children's daily routines, aiming at identifying potential indoor air pollutants and obtain valuable information about the contribution of each indoor microenvironment to the global daily exposure and the inhaled dose of air pollutants in children. High priority pollutants were monitored through passive techniques in 18 indoor microenvironments associated with 3–12-year-old schools, 12-18-year-old schools, and private homes located in Southern Spain. Air pollutant concentrations are compared with the recommended indoor air guideline values (IAGVs) reported by different standards and health organisations. The results show adequate indoor air quality values, within the ranges recommended by guidelines, and highlight the importance of monitoring benzene and formaldehyde to minimise adverse health effects, especially in homes, whose microenvironments are responsible for 88% of the inhaled dose of measured VOCs and aldehydes. Moreover, special attention should be taken of bedrooms, whose air pollutant concentrations are responsible for approximately 60% of the total inhaled dose of VOCs and aldehydes in children. Specific measures should be considered by public health authorities and other policymakers on how to develop and strengthen indoor air quality policy to protect and promote health in the housing stock. Highlights: Contribution of indoor spaces to the daily inhaled dose of air pollutants in children. Passive IAQ monitoring in 18 indoor microenvironments: schools and homes. Bedrooms are responsible for 60% of the daily inhaled dose of air pollutants. Importance of monitoring benzene and formaldehyde to minimise adverse health effects. Tremendous need to bring this research target into more attention.